The Competence and Job Description At Cicendo Eye Hospital Bandung - Hapsari, Ayuningtyas Yuli; Romdhoni, Ahmad (Universitas Pamulang, 2022)
A nurse and administrative employee must not only be able to provide medical care and services but must be able to master the skills of communicating well with patients to create a harmonious relationship between nurses or administrative employees and patients. (HR) quality and ability to compete and it is necessary to manage human resources properly so that the management will be right on target. This study aims to determine how employee's and nurses' competencies, job descriptions, and work motivation at Cicendo Eye Hospital Bandung, as well as the influence of competence on employee and nurse work motivation at Cicendo Eye Hospital Bandung, and the effect of job descriptions on work motivation at Cicendo Eye Hospital Bandung of the employees and nurses at Cicendo Eye Hospital Bandung. The descriptive and verification methodologies were utilized in the research. All personnel and nurses at Cicendo Eye Hospital Bandung were included in this study's sample. Multiple linear regression, coefficient of determination analysis, and hypothesis testing are used to process data. Based on the findings of the study, it can be concluded that competence has a positive and significant impact on employee and nurse motivation at Cicendo Eye Hospital Bandung, and that job description has a positive and significant impact on employee and nurse motivation at Cicendo Eye Hospital Bandung.